Susceptibilidad a deslizamientos en la parroquia San Carlos de las Minas perteneciente al cantón Zamora provincia de Zamora Chinchipe, a escala 1:10 000 - Cuenca Conza, Stefany Johanna (2022)
Landslide susceptibility is a very useful analysis for decision making, especially in the early stages of planning a project. In this sense, the purpose of this study is to assess the susceptibility of landslides in the rural parish of San Carlos de las Minas, Zamora canton, Zamora Chinchipe province; in an area of 150 km2. Using Geographic Information Systems (GIS) tools, this analysis will be expressed in an absolute thematic map in a scale of 1:10,000. The methodology used for cartographic preparation of the analysis is the method of the Hierarchical Analysis Process (Analytical Hierarchy). Process, AHP), postulated by Thomas Saaty in 1980; which is a quantitative method. To do the susceptibility map, the ArcGIS 10.6.1 program was used, in which weights were assigned to the different determining variables (Geomorphology, lithology, slopes, vegetation cover, drainage density and isohyets). Likewise, using the ArcMap tools, the field data was analyzed, correlated and interpreted. Which allowed sectorizing the land into homogeneous areas to qualify each of these areas according to the real or potential degree of susceptibility. The data collected, obtained and presented in this research constitute a valuable tool that is focused on improving the current conditions of the sector. In addition, this project can be the basis for the development of new studies, which are focused on choosing the best decisions to implement the corresponding mitigation and prevention works. Keywords: landslide susceptibility, mapping, conditioning factors, ArcMap tools.